THE APPLICATION OF THE FLIPPED CLASSROOM MODEL TO IMPROVE CRITICAL THINKING SKILLS OF 8TH GRADE STUDENTS ON LINEAR INEQUALITIES IN ONE VARIABLE - Rizki Sidiq Permana; Eyus Sudihartinih; Tia Purniati; Suhendra Suhendra; Ruswan Dallyono (Program Studi PGSD Universitas Flores, 2026)
Critical thinking skills of junior high school students in mathematics, particularly in Linear Inequalities in One Variable (LIOV), remain in the low category because students often follow mechanical procedures without in-depth analysis. This study aims to examine whether the application of the flipped classroom model can improve students’ critical thinking skills specifically in LIOV material. This quantitative study employed a quasi-experimental nonequivalent control group design involving 60 eighth-grade students in West Bandung Regency, divided into experimental and control groups. Data were collected using an essay-type critical thinking test and observation sheets, then analyzed using N-Gain scores and the Mann-Whitney U test. The results showed that the average N-Gain for the experimental group (0.680) was significantly higher than the control group (0.319), with a significance value of 0.000. The study concludes that the flipped classroom model is effective in improving critical thinking skills in LIOV through structured phases of independent exploration and collaborative in-class activities. This research implies that the flipped classroom model serves as a relevant instructional alternative to foster higher-order thinking skills and systematic problem-solving in mathematics education.